Morphosedimentary evolution of a beach spit system (Punta Rasa, Argentina) - Guisado Pintado, Emilia (2024)
Spits constitute sand-rich, elongated barriers extending laterally through the construction ofprogradational beach-ridges. Spits are constructed by angular wave approach and longshorecurrents, which results in the transport of sediment to the spit end and hence their growth. Ifsediment supply isn’t enough cannibalization can occur causing a narrowing and further breachingof the spit. One of the main controlling factors of sediment supply to spits are waves andparticularly high energy events such as storms.The spit of Punta Rasa, located in the northeast coast of the Buenos Aires province, represents thecoastal outer extreme of the Río de La Plata estuary. Towards the north the spit is bordered by thesouthern extreme of the Samborombón Bay, whereas, to the south, the spit extents along theOriental Barrier which ends towards the locality of Punta Medanos. The wave-built depositsinteract with marshes and tidal channels transgressing the shoreline from the north. Besides, thecoastal plain exhibits the interaction between beach-ridge systems, dune fields and sandybeaches.In this work, coastline changes and recent evolution of the system of spits in Punta Rasa areanalyzed using sedimentalogical profiles and aerial photographs. Results show an evolutionmarked by periods of erosion and significant changes in its morphology. Firther a general trend(since approx. 500 years) of the spit to curve towards the internal part of Bay is also found whichcould indicate a deficit in the contribution of sediment among with increasing mean sea level.